ANALYSIS OF FACTORS AFFECTING EMPLOYEE SATISFACTION AND ITS IMPLICATIONS ON JOB PERFORMANCE IN INFORMATION TECHNOLOGY WORKERS - Kurniawan, Indra; Erdiansyah, Rezi (Graduate Program of Universitas Tarumanagara, 2023)
During the pandemic, there was a change in work methods which caused the company and employees to start adapting to the new work system to maintain the company's performance. Because there has been a change in the work system from conventional to a flexible work system due to the COVID-19 pandemic, researchers want to examine the relationship between work life balance, employee benefits and remote working, what impact can there be with changes to the previous work system for conventional work systems, into a flexible work system and its relationship to employee satisfaction so that it is ultimately related to job performance. Previous studies have shown that work-life conflict has a negative impact on employee job performance. The main objective of this study is to obtain the relationship and role of the factors that can affect worker satisfaction, as well as what impact this has on employee performance. The research method used to explain the relationship between variables in this study is descriptive quantitative. From the research results, it was found that job performance will be even better if employee satisfaction is achieved, as mediation of work life balance, employee benefits and remote working. Although the three independent factors can also affect employee performance directly, the results of the research show that better results will be achieved if worker satisfaction is achieved first so that even better employee performance will be achieved as a result of the work methods adopted after COVID-19.